Continued Reduction in the Prevalence of Retinopathy in Adolescents With Type 1 Diabetes: Role of insulin therapy and glycemic control - Downie, Elizabeth (American Diabetes Association, 2011)
OBJECTIVE: To examine trends in microvascular complications in adolescents with type 1 diabetes between 1990 and 2009 in Sydney, Australia. RESEARCH DESIGN AND METHODS: We used analysis of complications in 1,604 adolescents (54% female, aged 12–20 years, median duration 8.6 years), stratified by four time periods using Generalized Estimation Equations as follows: T1 (1990–1994), T2 (1995–1999), T3 (2000–2004), and T4 (2005–2009). Early retinopathy was detected using seven-field fundal photography, albumin excretion rate (AER) using timed overnight urine collections, and albumin-to-creatinine ratio (ACR) and peripheral nerve function using thermal and vibration threshold. RESULTS: Retinopathy declined (53, 38, 23, and 12%; P < 0.001), as did borderline elevation of AER/ACR (45, 30, 26, and 30%; P < 0.001) and microalbuminuria (8, 4, 3, and 3%; P = 0.006). Multiple daily injections (MDI)/continuous subcutaneous insulin infusion (CSII) use increased (17, 54, 75, and 88%; P < 0.001), median HbA(1c) decreased (9.1, 8.9, 8.5, and 8.5%; P < 0.001), and severe hypoglycemia was unchanged (6, 8, 10, and 7%; P = 0.272). Retinopathy was associated with diabetes duration (odds ratio [OR] 1.12 [95% CI 1.08–1.17]), age (1.13 [1.06–1.20]), HbA(1c) (1.16 [1.08–1.25]), systolic blood pressure (BP) SDS (1.31 [1.16–1.48]), socioeconomic disadvantage (1.42 [1.04–1.95]), and 1 to 2 injections per day (vs. MDI/CSII; 1.35 [1.05–1.73]); borderline AER/ACR with male sex (1.32 [1.02–1.70]), age (1.19 [1.12–1.26]), HbA(1c) (1.18 [1.08–1.29]), weight SDS (1.31 [1.21–1.53]), insulin dose per kilograms (1.64 [1.13–2.39]), 1 to 2 injections per day (1.41 [1.08–1.84]), and socioeconomic disadvantage (1.68 [1.23–2.31]); and microalbuminuria with age (1.14 [1.01–1.29]), HbA(1c) (1.20 [1.05–1.37]), diastolic BP SDS (1.76 [1.26–2.46]), and 1 to 2 injections per day (1.95 [1.11–3.41]). CONCLUSIONS: The decline in retinopathy supports contemporary guidelines that recommend lower glycemic targets and use of MDI/CSII in children and adolescents with type 1 diabetes.